WRITTEN SOURCES ON THE ARTS AND CRAFTS OF MEDIEVAL KHOREZM (TAMADDUN NURI JURNALI, 2025)
This article analyzes the development history of medieval Khorezm handicrafts based on written sources. During the 9th-13th centuries, Khorezm was one of the important centers for trade, handicrafts, and cultural life, with its handicraft industries distinguished by the production of a variety of products. Written sources, including works by Arab and Persian authors, provide valuable information about Khorezmian handicrafts, raw material sources, and product types. Artisans achieved significant advancements in fields such as metallurgy, weaponry, textile production, leatherworking, and the processing of precious stones. Khorezmian products were highly valued in both domestic and foreign markets, making the region a crucial center of the Central Asian economy. The article also examines the stages of development, production processes, and the significance of handicraft products based on archaeological finds and historical documents. This research serves to provide a deeper understanding of the role of Khorezmian handicrafts in the economic and cultural life of the region.